Big Five Personality Traits as Predictors of Teachers Perceived Character Education Effectiveness: Evidence from Indonesian Schools - Waode Emilya Megawati; Sarimanah Eri; Eka Suhardi (Lembaga Sosial Rumah Indonesia, 2026)
Purpose – This study examines the association between Big Five personality traits and teachers perceived character education effectiveness. Although prior research has established the role of personality in teaching, limited attention has been given to the relative contribution of each trait, particularly in non-Western contexts. Methods – A quantitative cross-sectional survey design was employed, involving 197 teachers from Indonesian schools selected through multistage random sampling. Personality traits were measured using a validated Big Five instrument based on the Five-Factor Model, while perceived character education effectiveness was assessed through a multidimensional scale capturing implementation quality, school climate, and student character development. All measures demonstrated acceptable internal consistency (Cronbach’s ? > 0.70). Data was analyzed using multiple regression and relative weight analysis (RWA). Findings – The model explained 34.6% of the variance in perceived character education effectiveness. Emotional stability, conscientiousness, and openness to experience showed significant positive associations. Among these, emotional stability contributed the largest proportion of explained variance, followed by conscientiousness and openness. Extraversion and agreeableness showed smaller and non-significant effects. Research Implications – These findings suggest that personality traits are differentially associated with teachers’ perceptions of character education effectiveness. Practically, the results suggest the potential relevance of emotional regulation, consistency, and adaptability in supporting character education practices. However, the cross-sectional design and reliance on self-reported data limit causal interpretation and may introduce common method bias. Future research should employ longitudinal designs and multi-source data to strengthen the robustness of these findings.